Historical ethnobotany: an overview of selected studies - Silva, Taline Cristina da (2014)
Historical Ethnobotany is an area of research responsible for understanding past interrelationships between people and plant using written records and iconography. The literature on this topic is scattered, and many of these studies are not recognised as such; therefore, it is difficult to compile historical ethnobotanical data. Accordingly, this study attempted to draw a general picture of the publications in this field. The Scopus, ISI Web of Knowledge and Scirus databases were used to search for articles with such keywords as “Ethnobotany + History” and “Historical Ethnobotany” among others. After the studies were selected, information was extracted that included the continents addressed and historical ages. Most studies encompassed a time frame that began in the Modern Age (54.7%), and 46% of the studies were focused on the American continent. With regard to the nature of the source, 98% of the studies included written records, and publications that used the documental analysis as a secondary data in their scope of research were among the most frequent types of studies that were found. In respect to iconographic sources, paintings were used in 6% of the studies. A total of 66% of the studies involved a species or species group as the study object. Our survey revealed the vast scope of these Historical Ethnobotany studies. We believe that this scientific field has great potential for future development and that its findings will only grow in importance considering the current ethnobotanical debate